AYAH DALAM SENI LUKIS REALIS KONTEMPORER - Ratna Fadilah; Erfahmi Erfahmi (Serupa The Journal of Art Education, 2021)
The creation of this final work served to visualize the role of a good father to his children as an idea for the creation of contemporary realist artwork. The methods and processes of the work used in the creation of these contemporary realist works of art are a few steps that are: (1) Preparation, (2) Elaborate, (3) Synthesis, (4) realization of concept, and (5) Completion. This work visualizes two human objects, namely the father and son figures, and several other supporting objects such as the al-quran, books, motorbikes, prings, balloons, and others. This work reveals the role of good father for his children. The author succeeded in realizing ten paintings with titles: Supervisor I, Supervisor II. Supervisor III. Role model, Motivator, Protector, Attention, Affection, Friend, A playmate.Keywords: Father, Art, Paint, Contemporary Realist.